Risk Factor for Chronic Kidney Disease in Internist Polyclinic Patient at Rumah Sehat Terpadu Dompet Dhuafa Hospital in 2021 - Dessy Marlinda Cahaya; Munaya Fauziah (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Based on the data reports of Riset Kesehatan Dasar, the national prevalence of CKD in Indonesia is 0.38%. The province of West Java is in the 8th rank of 34 other provinces, its prevalence is 0.48%. The number of new cases of CKD at the Rumah Sehat Terpadu Dompet Dhuafa Hospital in 2020 increased from 47 people to 51 people. The object of this study is to identify the risk factors that can affect the incidence of CRF in the Rumah Sehat Terpadu Dompet Dhuafa Hospital, the Year 2021. Case-control design with 91 respondents as the control group and 91 respondents as the case group, the source of the data come from the medical records of RST DD Hospital. The sampling technique used is simple random sampling. The data analysis technique used is the chi-square test with = 0.05. The influence of a history of diabetes mellitus (p-value = 0.002; OR :2.810; 95%CI: 1.493 – 5.287), history of hypertension (p-value = 0.005; OR :2.796; 95%CI: 1.407 – 5.557), history of obstructive nephropathy (p-value = 0.018; OR: 0.205; 95%CI: 0.056 – 0.744) against CKD. The risk factors that influence the incidence of CKD in the Rumah Sehat Terpadu Dompet Dhuafa Hospital are a history of diabetes Mellitus, hypertension, and obstructive nephropathy. The community must implement the Pola Hidup Bersih dan Sehat as their lifestyle. Health workers need to give an education on health to the community, especially for at-risk populations.